Teacher Motivation and Job Satisfaction: The Impact of Job Satisfaction and Motivation on Teacher Performance (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Levelsof job satisfaction and motivation were measured by survey in a sample of 50teachers. A sample of 12 teachers was then studied using the Experience Sam-pling Method (ESM). Job satisfaction and motivation correlated significantlywith responsibility levels, gender, subject, age, years of teaching experience,and activity. For this group of teachers who work in a school with a selectivestudent body, overall motivation and job satisfaction levels were high. Basedupon the findings, it appears that gratifica- tion of higher-order needs ismost important for job satisfaction.